Pertanggungjawaban Online Shop Menggunakan Konten Endorsment Orang Lain Tanpa Izin Di Instagram Untuk Kepentingan Komersial - Alif Wildan Anugrah; Adhitya Widya K (Jurnal Hukum dan Sosial Politik, 2023)
The purpose of this research is to determine the responsibility of online stores that use other people's endorsement content without permission on Instagram for commercial purposes and to find what legal remedies can be taken by influencers whose endorsement content is misused by other people without permission. Instagram for commercial purposes. This type of research is norrmative juridical, data analysis uses norm ative research methods through library research and secondary data review. The data collection method used is literature studyy with data sources of primary legal materials and secondary legal materials. The results of this research are that the use of endorsement content by other online shops outside the agreement has violated the moral rights and economic rights of endorsement content creators as regulated in Article 9 paragraph (1) letters a, b, c and/or g for commercial use as well as Article 9 paragraph (2) Law no. 28 of 2014. Based on Article 113 paragraph (3) of Law no. 28 of 2014, the legal remedy that can be taken is to try to comment on the post and ask other online stores to delete it. You can also settle the lawsuit in the competent court in the country that has jurisdiction to try the lawsuit, namely Indonesian law.